Bioengineered Multicellular Liver Microtissues for Modeling Advanced Hepatic Fibrosis Driven Through Non‐Alcoholic Fatty Liver Disease. Issue 14 (9th March 2021) - Cho, Hyun‐Jong; Kim, Han‐Jun; Lee, KangJu; Lasli, Soufian; Ung, Aly; Hoffman, Tyler; Nasiri, Rohollah; Bandaru, Praveen; Ahadian, Samad; Dokmeci, Mehmet R.; Lee, Junmin; Khademhosseini, Ali
Abstract: Despite considerable efforts in modeling liver disease in vitro, it remains difficult to recapitulate the pathogenesis of the advanced phases of non‐alcoholic fatty liver disease (NAFLD) with inflammation and fibrosis. Here, a liver‐on‐a‐chip platform with bioengineered multicellular liver microtissues is developed, composed of four major types of liver cells (hepatocytes, endothelial cells, Kupffer cells, and stellate cells) to implement a human hepatic fibrosis model driven by NAFLD: i) lipid accumulation in hepatocytes (steatosis), ii) neovascularization by endothelial cells, iii) inflammation by activated Kupffer cells (steatohepatitis), and iv) extracellular matrix deposition by activated stellate cells (fibrosis). In this model, the presence of stellate cells in the liver‐on‐a‐chip model with fat supplementation showed elevated inflammatory responses and fibrosis marker up‐regulation. Compared to transforming growth factor‐beta‐induced hepatic fibrosis models, this model includes the native pathological and chronological steps of NAFLD which shows i) higher fibrotic phenotypes, ii) increased expression of fibrosis markers, and iii) efficient drug transport and metabolism. Taken together, the proposed platform will enable a better understanding of the mechanisms underlying fibrosis progression in NAFLD as well as the identification of new drugs for the different stages of NAFLD. Abstract : In this paper, a human non‐alcoholic fatty liver disease (NAFLD)‐on‐a‐chip platform containing bioengineered primary multicellular liver microtissues is developed for modeling hepatic fibrosis driven by NAFLD. These results from the suggested platform shed light on the role of the design strategy of liver disease models in accurately detecting disease progression and identifying potential drug candidates more effectively.